Domestiquer la norme mondiale. Brevet pharmaceutique, bonnes pratiques de fabrication et contrôle du prix des médicaments en Inde - Yves-Marie Rault-Chodankar (L'Espace Politique)
The construction and circulation of international norms aimed at controlling drug manufacturing and marketing practices is often analyzed through the prism of North/South, patented/generic, public/private, global/national/local oppositions. This article draws on interviews with key players in the pharmaceutical sector in India to demonstrate that these binary oppositions mask the diversity of relationships maintained locally with global standards. Taking the case of a patented molecule, Sofobusvir, we discuss how Indian generic companies adjust to the international law on intellectual property and how the smallest firms justify transgressing norms while taking advantage of their existence. Analyzing the role of the drug control agency of the state of Gujarat, we also show that the application of Indian good manufacturing practices is negotiated with the different levels of the local administration, between health needs and industrial attractiveness. We also identify the different attitudes of the companies and the central state towards drug pricing standards to highlight their strong capacities for adaptation, subversion, and diversion of norms. Overall, this article highlights the various relationships to norms to explain their continued diversity on a global scale.